Functional thyroid disorders in the pharmacy setting – how can we help our patients? - Pecikoza, Uroš (Archives of Pharmacy, 2022)
Functional thyroid disorders (hypothyroidism and hyperthyroidism) are amongst the most common endocrine disorders pharmacists encounter on a daily basis. They are highly prevalent in iodine-replete areas, and affect women about 10 times more often than man. Hypothyroidism (thyroid hormone deficiency) is usually caused by Hashimoto’s thyroiditis, an autoimmune disorder that leads to gradual thyroid destruction. The drug-of-choice for treating hypothyroidism is levothyroxine, a synthetic form of thyroxine. Key points which need to be discussed with patients who are prescribed levothyroxine for the first time are when/how to administer this drug, how its effects are monitored, what drugs may affect its efficacy, and the importance of properly treating hypothyroidism during pregnancy. Hyperthyroidism (increased production of thyroid hormones) is most often caused by Graves’ disease, another thyroid autoimmune disorder in which stimulatory autoantibodies against the TSH receptor lead to increased thyroid function. Graves’ disease is most commonly treated with thionamide drugs (thiamazole, carbimazole or propylthiouracil) and patients using these drugs should be advised on the monitoring requirements, duration of treatment, and how to recognize possible serious adverse effects (agranulocytosis and hepatotoxicity), and informed that these drugs must be used during pregnancy in order to reduce the risk of adverse outcomes for the mother and baby.
Keywords: hypothyroidism; hyperthyroidism; levothyroxine; thionamide drugs